Studi Fenomenologi Tantangan dan Solusi Kreatif Perawat Case Manager dalam Meningkatkan Kualitas Pelayanan Pasien di Rumah Sakit - Agustin Faidhatul Ulfa, Widya; Agustin, Ratna; Agustiningsih, Ida (Indonesian Academia Health Sciences Journal, 2024)
Background: One of the service models to maintain the quality of service in the Hospital is case management, driven by the Case Manager who is generally responsible for the coordination and continuity of patient services. However, over time, the Case Manager profession has not been optimal in implementing its roles and functions, causing problems in services, namely lack of continuity of service, ineffective management of patient flow, and lack of efficiency of service costs that affect the quality of service. The purpose of this study is to describe the Case Manager's strategy in implementing its role and function to improve the quality of service at Siti Khodijah Sepanjang Hospital. Methods: The type of qualitative research with a phenomenological approach, the number of Case Manager and PPA informants is 6, data is obtained through in-depth interviews, observation and documentation. Results: The Based on the research results, 6 themes were obtained, namely qualifications, role and function implementation strategies, completeness of documents, readiness of reporting systems, quality of service, and obstacles. The implementation of the role and function of the Case Manager has been running well but has not been optimal because there are still obstacles, namely the adequacy of the number of Case Manager HR, multi-roles, and patient complaints. The strategy carried out by the Case Manager is to collaborate with patients and families and coordinate with the head of the room, unit team, related DPJP so that the Case Manager can monitor the patients they manage, and coordinate with casemix for financing. Conclusion: Case Manager's strategy in implementing its roles and functions is important in helping to improve the quality of service. The dominant roles and functions are the cost control role and the service coordination function